The Anticancer Peptide TAT-RasGAP317−326 Exerts Broad Antimicrobial Activity - Heulot, Mathieu; Jacquier, Nicolas; Aeby, Sébastien; Le Roy, Didier; Roger, Thierry; Trofimenko, Evgeniya; Barras, David; Greub, Gilbert; Widmann, Christian (Frontiers in Microbiology, 2017)
Antibiotic resistance has become a major health issue. Nosocomial infections and the prevalence of resistant pathogenic bacterial strains are rising steadily. Therefore, there is an urgent need to develop new classes of antibiotics effective on multi-resistant nosocomial pathogenic bacteria. We have previously shown that a cell-permeable peptide derived from the p120 Ras GTPase-activating protein (RasGAP), called TAT-RasGAP317-326, induces cancer cell death, inhibits metastatic progression, and sensitizes tumor cells to various anti-cancer treatments in vitro and in vivo. We here report that TAT-RasGAP317-326 also possesses antimicrobial activity. In vitro, TAT-RasGAP317-326, but not mutated or truncated forms of the peptide, efficiently killed a series of bacteria including Escherichia coli, Acinetobacter baumannii, Staphylococcus aureus and Pseudomonas aeruginosa. In vivo experiments revealed that TAT-RasGAP317-326 protects mice from lethal E. coli-induced peritonitis if administrated locally at the onset of infection. However, the protective effect was lost when treatment was delayed, likely due to rapid clearance and inadequate biodistribution of the peptide. Peptide modifications might overcome these shortcomings to increase the in vivo efficacy of the compound in the context of the currently limited antimicrobial options.